2011
DOI: 10.4318/tjg.2011.0179
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and histopathological findings in patients with dyspepsia

Abstract: respectively). Atrophy was found in 27 (5.5%) of all cases (in 10 Helicobacter pylori (-) patients and in 17 Helicobacter pylori (+) patients), but no significant relation was found with increasing Helicobacter pylori intensity (p>0.05). There was no significant difference between corpus alone or antrum alone Helicobacter pylori (+) and both corpus/antrum (+) patients in regards to the presence of activity, inflammation, intestinal metaplasia, and atrophy (p>0.05). Conclusions: Determination of the degree of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
5
2
0
Order By: Relevance
“…Instead, activity and chronic inflammation in the antrum, as well as in the corpus significantly improved in the responders, but not in the non-responders, suggesting that H. pylori -induced inflammation mediates dyspeptic symptoms, but not atrophy itself. Our results could be supported by the report that the activity and inflammation increased with increase of H. pylori intensity in patients with dyspepsia 46. In addition, H. pylori -positive FD patients with 'antrum predominant' chronic gastritis showed symptom improvement at 1 year after the successful eradication 3.…”
Section: Discussionsupporting
confidence: 89%
“…Instead, activity and chronic inflammation in the antrum, as well as in the corpus significantly improved in the responders, but not in the non-responders, suggesting that H. pylori -induced inflammation mediates dyspeptic symptoms, but not atrophy itself. Our results could be supported by the report that the activity and inflammation increased with increase of H. pylori intensity in patients with dyspepsia 46. In addition, H. pylori -positive FD patients with 'antrum predominant' chronic gastritis showed symptom improvement at 1 year after the successful eradication 3.…”
Section: Discussionsupporting
confidence: 89%
“…As in our study, Basir, et al also found a significant relationship between H. pylori colonization intensity and chronic gastritis activity [20]. In a study performed by means of Histopathological examination of endoscopic biopsy specimens of 461 patients, Türkay, et al reported that as the intensity of H. pylori increased, the intensity of inflammation increased, too [21]. In a study conducted by Alagöz, et al a significant correlation was observed between H. pylori severity and lymphoplasmacytic cell infiltration and inflammation activation [22].…”
Section: Methodssupporting
confidence: 84%
“…In a previous study, the ratio of chronic gastritis and glandular metaplasia had been found in cirrhotic patients as follows: 15.6% of patients of Child-Pugh A, 70% of Child-Pugh B, and 100% of Child-Pugh C [23]. In a Turkish study on patients with dyspepsia, atrophy was found in only 5.5% of cases [24]. In our study, the incidence of atrophy and intestinal metaplasia was approximately 13%.…”
Section: Discussionsupporting
confidence: 55%